Nanocomposite ultra-early strength polycarboxylate water reducer, preparation method and application thereof
By introducing early strength functional monomers onto the polyether large monomer and optimizing the synthesis process, nanocomposite ultra-premature strength polycarboxylic acid water reducer was prepared, which solved the problems of high energy consumption, large particle size and poor dispersion in the preparation process of the existing water reducer, achieving efficient early strength performance and improved durability.
Patent Information
- Application Number
- CN202411708588.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing early-strength polycarboxylic acid water reducing agents have problems such as high energy consumption, large particle size, poor dispersion and poor durability during the preparation process, and cannot meet the needs of early-strength and ultra-strong concrete in actual applications.
By introducing early-strengthening functional monomers, the molecular structure of the polyether large monomers is designed, the synthesis process is optimized, and the nanocomposite ultra-stength polycarboxylic acid water reducing agent is prepared. The method includes adding polyether macromonomer, reducing agent, functional monomer, oxidizing agent and deionized water at a specific temperature, then dropwise addition of acrylic acid solution and vitamin C aqueous solution, adjusting the reaction system to alkalinity, then adding calcium nitrate and sodium silicate, and stirring the reaction to obtain the finished product.
The prepared nanocomposite ultra-premature strength polycarboxylic acid water reducing agent has suitable water reduction rate, excellent early strength effect, improved apparent quality of concrete and improved durability, which significantly improves the early strength and permeability of concrete.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete water reducing agents, and in particular to a nano composite ultra-early strength polycarboxylate water reducing agent, a preparation method and application thereof. Background Art
[0002] As an important way to realize prefabricated buildings, precast concrete technology has the characteristics of reducing construction pollution, improving construction efficiency and quality, and can better reflect the advantages of green construction. With the implementation of relevant policies and the promotion of advanced technologies, the market demand for precast concrete components is increasing day by day. Concrete components must not only have excellent mechanical properties, but also achieve the major goal of energy conservation and emission reduction in the industry. This puts high demands on the production of precast concrete components, which not only accelerates the turnover of templates and speeds up production efficiency, but also ensures the early strength and later strength development of precast concrete components. Therefore, improving the early strength of precast concrete components has become a technical key. The means to improve the early strength performance of components include reducing the water-cement ratio, increasing the amount of cement or using high-strength grade cement, adding early strength agents, etc. However, the above methods are not ideal, which will have an adverse effect on the later durability and volume stability of concrete, and the economy is also relatively poor. Therefore, developing an early strength water reducer that can improve the early strength of concrete components without affecting the workability and later volume stability of concrete has become an important research direction in the field of polycarboxylate water reducers at this stage.
[0003] As the third generation of water reducers, polycarboxylate water reducers have the advantages of high water reduction rate, small slump loss, good compatibility with cement, and designable molecular structure. They are the most widely used water reducers on the market. There are two main methods for preparing early-strength polycarboxylate water reducers: one is to compound ordinary polycarboxylate water reducers with early strength agents. For example, patent CN102775088A proposes a mud-blocking concrete water reducer and a preparation method, which is compounded with quaternary ammonium salt soil stabilizer, inorganic potassium salt, organic phosphorus scale inhibitor and polycarboxylate water reducer. This type of compounded early strength agent has certain problems in current applications, such as the compounded product has the disadvantages of poor stability, compatibility and large dosage, too high alkali content will produce alkali-aggregate reaction, and chloride salts are easy to cause steel corrosion, which are not conducive to the durability of concrete. Among organic substances, alcohol amine early strength agents are expensive and the dosage is difficult to control, so the cost performance is not high; the other is to synthesize an early strength polycarboxylic acid water reducer with early strength performance. The Chinese patent with application number 201811354821.X discloses a preparation method of an early strength polycarboxylic acid water reducer. Although the synthesis temperature of the early strength polycarboxylic acid water reducer is relatively low, at 40°C, the synthesis time is 3 to 3.5 hours, and the energy consumption is still high, which is not conducive to promotion. The products prepared by the above two preparation methods have a large particle size, which makes the apparent quality of the product need to be improved, and also limits the dispersibility and water reduction effect of the product, thereby affecting the fluidity and compressive performance of the product.
[0004] In summary, the research on early-strength polycarboxylate water-reducing agents is still relatively lacking. The research on polycarboxylate water-reducing agents that truly achieve early strength from the perspective of polymer molecular structure design is still in the exploratory stage. There are few mature products, which cannot meet the needs of early-strength and ultra-early-strength concrete in practical applications, greatly limiting the application of polycarboxylate water-reducing agents in precast concrete. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a nano-composite ultra-early strength polycarboxylate water reducer, a preparation method and its application. The present application introduces an early strength functional monomer, designs the molecular structure of the polyether macromonomer, optimizes the synthesis process, and prepares a nano-composite ultra-early strength polycarboxylate water reducer with suitable water reduction rate, good early strength effect and improved concrete surface quality.
[0006] To achieve the above-mentioned object and other related objects, the present invention provides a method for preparing a nano-composite ultra-early strength polycarboxylate water reducer, which is characterized by comprising the following steps:
[0007] Step 1, add a polyether macromonomer, a reducing agent, a functional monomer, an oxidant, and deionized water into a reaction container, and stir at 25-45° C. until all are dissolved to obtain a reaction solution A;
[0008] Step 2, at 25-45° C., simultaneously adding an acrylic acid solution and a vitamin C aqueous solution to a stirred reaction solution A, raising the temperature to 45-65° C. after the addition is completed, and carrying out a heat preservation reaction for a period of time, and adjusting the reaction system to alkalinity with an alkaline compound and / or an aqueous solution of an alkaline compound to obtain a reaction solution B;
[0009] Step 3: Add calcium nitrate aqueous solution and sodium silicate aqueous solution to reaction solution B at 0-10° C., stir and react for 30-60 minutes to obtain a finished product.
[0010] As a preference of the present application, the polyether macromonomer is alkylene polyoxyethylene ether.
[0011] As a preference of the present application, the molar ratio of the polyether macromonomer to acrylic acid is 1:4.0-5.0.
[0012] As a preference of the present application, the molar ratio of the polyether macromonomer to acrylic acid is 1:4.5.
[0013] As a preference of the present application, the mass ratio of the polyether macromonomer to the reducing agent is 1:0.018-0.023.
[0014] As a preference of the present application, the mass ratio of the polyether macromonomer to the reducing agent is 1:0.021.
[0015] As a preference of the present application, the reducing agent is sodium hypophosphite.
[0016] As a preferred embodiment of the present application, the oxidant is H2O2 with a mass concentration of 30%.
[0017] As a preference of the present application, the functional monomer is one or more of N,N-dimethylacrylamide (DMAA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), and N-hydroxymethylacrylamide (HAM).
[0018] As a preferred embodiment of the present application, the functional monomers are 2-acrylamide-2-methylpropane sulfonic acid and N-hydroxymethyl acrylamide, wherein the mass ratio of 2-acrylamide-2-methylpropane sulfonic acid to N-hydroxymethyl acrylamide is 1:2-4.
[0019] As a preference of the present application, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid to N-hydroxymethyl acrylamide is 1:3.
[0020] As a preference of the present application, the mass ratio of the functional monomer to the polyether macromonomer is 0.2-0.4:10.
[0021] As a preference of the present application, the mass ratio of the functional monomer to the polyether macromonomer is 0.3:10.
[0022] As a preferred embodiment of the present application, in step 2, the alkaline compound is sodium hydroxide or potassium hydroxide, more preferably sodium hydroxide.
[0023] As a preferred embodiment of the present application, in step 2, the aqueous solution of the alkaline compound is a sodium hydroxide aqueous solution with a mass concentration of 30-35%. More preferably, the mass concentration of the sodium hydroxide aqueous solution is 32%.
[0024] As a preferred embodiment of the present application, in step 2, the total time of dropwise addition is controlled within 1 to 3 hours; the insulation reaction temperature is 55° C., the insulation reaction time is 20 to 50 minutes, and the alkaline compound and / or the aqueous solution of the alkaline compound is used to adjust the pH of the reaction system to 9 to 12.
[0025] As a preferred embodiment of the present application, in step 2, the total dropwise addition time is controlled at 1.5 h, the insulation reaction time is 30 min, and the alkaline compound and / or the aqueous solution of the alkaline compound is used to adjust the pH of the reaction system to 11.7.
[0026] As a preferred embodiment of the present application, in step 2, the mass concentration of acrylic acid is 35% to 45%.
[0027] As a preferred embodiment of the present application, in step 2, the mass concentration of acrylic acid is 40%.
[0028] As a preferred embodiment of the present application, in step 2, the mass concentration of the vitamin C aqueous solution is 0.5%~1.5%.
[0029] As a preferred embodiment of the present application, in step 2, the mass concentration of the vitamin C aqueous solution is 1.0%.
[0030] As a preferred embodiment of the present application, the mass ratio of polyether macromonomer, calcium nitrate and sodium silicate is 10: (0.08-0.12): (0.07-0.09).
[0031] As a preference of the present application, the mass ratio of polyether macromonomer, calcium nitrate and sodium silicate is 10:0.1:0.08.
[0032] As a preferred embodiment of the present application, in step 3, the mass concentration of the calcium nitrate solution is 30-50%.
[0033] As a preference of the present application, in step 3, the mass concentration of the calcium nitrate solution is 40%.
[0034] As a preferred embodiment of the present application, in step 3, the mass concentration of the sodium silicate solution is 10-20%.
[0035] As a preferred embodiment of the present application, in step 3, the mass concentration of the sodium silicate solution is 15%.
[0036] As a preferred embodiment of the present application, in step 3, the stirring rate is 120~200rpm.
[0037] As a preference of the present application, in step 3, the stirring rate is 160 rpm.
[0038] The invention also provides a nano-composite super-early-strength polycarboxylate water-reducing agent prepared by the preparation method of the nano-composite super-early-strength polycarboxylate water-reducing agent.
[0039] As the preferred embodiment of the present application, the nano-composite ultra-early strength polycarboxylate water reducer of the present application is inverted T-shaped, with a molecular weight distribution (Mw / Mn) of 2.0~2.2 and a particle size distribution of 10~30nm. The T-shaped morphology of the molecular chain allows the water reducer molecules to have a strong steric hindrance dispersion effect, while the long polyoxyethylene side chain allows water to enter the cement particles, promotes the hydration of cement, improves the flow properties of cement concrete, improves the early water reduction and dispersion effect, and enhances the early strength performance of the water reducer; the introduction of nano-silicon and nano-calcium particles promotes the formation of CSH phase during cement hydration. The earlier the CSH phase is formed, the higher the early strength of the hydration product. The two work together to accelerate the cement hydration rate, increase the hydration products, and make the cement paste structure more compact, thereby improving the impermeability of concrete, improving the durability of concrete, and improving the early strength of concrete. In addition, the composite functional monomers used in the present application can be compounded into a special inverted T shape through a specific range of ratios, and under alkaline conditions, it is beneficial to ensure that the nano-composite ultra-early strength polycarboxylate water-reducing agent does not produce agglomeration, agglomeration and the like, thereby forming a stable nanostructure, which significantly improves the stability and durability of the product.
[0040] The invention also provides an application of the nano-composite ultra-early strength polycarboxylate water reducer in concrete.
[0041] As a preferred embodiment of the present application, the application is characterized in that the dosage of the nano-composite ultra-early strength polycarboxylate water-reducing agent when applied to concrete is 0.1% to 0.5% of the weight of the concrete gel material.
[0042] As a preferred embodiment of the present application, the dosage of the nano-composite ultra-early strength polycarboxylate water-reducing agent when applied to concrete is 0.2% of the weight of the concrete gel material.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) The present invention uses alkylene polyoxyethylene ether to introduce functional monomers under a redox system to synthesize an inverted T-shaped early-strength polycarboxylate water-reducing agent with a long molecular side chain; then it is compounded with nano calcium silicate hydrate to obtain a nano composite super-early-strength polycarboxylate water-reducing agent with a special structure. In concrete applications, it not only has a low dosage, a high water reduction rate, and strong slump retention, but also has excellent anti-mud performance;
[0045] (3) The water reducer prepared by the present invention is in an inverted T shape, with a molecular weight distribution (Mw / Mn) of 2.0-2.2 and a particle size distribution of 10-30 nm. The T-shaped morphology of the molecular chain allows the water reducer molecules to have a strong steric hindrance dispersion effect while the long polyoxyethylene side chain allows water to enter the cement particles, promoting the hydration of cement and improving the early strength performance of the water reducer; the introduction of nano-silicon and nano-calcium particles promotes the formation of CSH phase during cement hydration. The earlier the CSH phase is formed, the higher the early strength of the hydration product. The two synergistically promote the acceleration of cement hydration rate and the increase of hydration products, which affects the hydration and coagulation and hardening process of cement, makes the cement paste structure more compact, and improves the early strength of concrete. After testing, the 1-day compressive strength ratio of the water reducer of the present application is ≥126%, the 3-day compressive strength ratio is ≥118%, and the standard curing time is 24 hours. The compressive strength of cement mortar at 90°C is 17MPa, and the compressive strength of concrete is 15.7MPa; the compressive strength of concrete cured at 90°C is 73.0MPa (C80 prefabricated pipe pile concrete), which has a significant early strength effect; and the nano-composite ultra-early strength polycarboxylate water-reducing agent particles of the present invention have strong stability and are not easy to agglomerate and precipitate; the total alkali content of the product is ≤2.0%, which avoids reaction with alkali aggregate in concrete and ensures the long-term durability and stability of the concrete; and the chloride ion content is ≤0.01%, which proves that the product prepared by the method is safe and durable.
[0046] (4) The reducing agent of the present invention is compounded with acrylic acid solution and vitamin C, which can reasonably regulate the reaction rate of the unsaturated polyether macromonomer, thereby improving the conversion rate of the polyether monomer and making the synthesized polycarboxylic acid water reducer have better early strength performance;
[0047] (5) The composite functional monomers used in the present application can be compounded into a special inverted T shape through a specific range of proportions, and under alkaline conditions, it is beneficial to ensure that the nano-composite ultra-early strength polycarboxylate water-reducing agent does not produce agglomeration, agglomeration and the like, thereby forming a stable nanostructure. In addition, the polymer covers the microstructure pores of the concrete, the porosity is reduced, and the density is increased, thereby improving the impermeability of the concrete, improving the durability of the concrete, and significantly improving the stability and durability of the product;
[0048] (6) The nanocomposite ultra-early strength polycarboxylic acid water-reducing agent particles of the present invention are highly stable and not prone to agglomeration and precipitation; the total alkali content of the product is ≤2.0%, which avoids reaction with alkali aggregates in concrete and ensures the long-term durability and stability of the concrete; and the chloride ion content is ≤0.01%, which proves that the product prepared by this method is safe and durable. Moreover, the concrete surface with the water-reducing agent of the present application is smooth, the gradation of the mortar is continuous, and the overall structure is more compact, which significantly improves the early strength effect of the concrete, and can effectively reduce the shrinkage of the concrete, greatly reducing the construction cost.
[0049] (7) The preparation method of the present invention has simple process, short reaction time, easy operation, high reaction efficiency, low energy consumption, short production cycle, and is easy for industrial production. DETAILED DESCRIPTION
[0050] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0051] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0052] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0053] Some of the raw materials used in the present invention are introduced as follows:
[0054] Alkylene polyoxyethylene ether was purchased from Wuhan Aoke Chemical Co., Ltd.
[0055] N,N-dimethylacrylamide was purchased from Shandong Dejurenhe Chemical Raw Materials Co., Ltd.
[0056] 2-Acrylamide-2-methylpropanesulfonic acid was purchased from Shandong Fantai Refining Biotechnology Co., Ltd.
[0057] N-Hydroxymethylacrylamide, Wuhan Rongcan Biotechnology Co., Ltd.
[0058] Sodium hypophosphite was purchased from Suzhou Lianxiong Chemical Technology Co., Ltd.
[0059] Acrylic acid was purchased from Shandong Xuchen Chemical Technology Co., Ltd.
[0060] Calcium nitrate was purchased from Jiangsu Yihai Xupu Chemical Co., Ltd.
[0061] Sodium silicate was purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0062] Vitamin C was purchased from Hebei Lihua Biotechnology Co., Ltd.
[0063] Example 1
[0064] The present invention provides a method for preparing a nano-composite ultra-early strength polycarboxylate water reducer, comprising the following steps:
[0065] Step 1, add 400 g of alkylene polyoxyethylene ether (0.08 mol), 8.5 g of sodium hypophosphite, 12 g of functional monomer, 3.5 mL of H2O2 with a mass concentration of 30%, and 360 mL of deionized water into a reaction container, and stir at 40°C until all are dissolved to obtain a reaction solution A; the functional monomer is a mixture of 2-acrylamide-2-methylpropane sulfonic acid and N-hydroxymethyl acrylamide, wherein the mass ratio of N,N-dimethylacrylamide, 2-acrylamide-2-methylpropane sulfonic acid and N-hydroxymethyl acrylamide is 1:3;
[0066] Step 2, at 40°C, simultaneously add 65 mL of 40% acrylic acid solution (0.36 mol) and 100 mL of 1.0% vitamin C aqueous solution to the stirred reaction solution A, and after the addition is completed, heat to 55°C for insulation reaction for 30 minutes, and adjust the reaction system to 11.7 with 32% sodium hydroxide aqueous solution to obtain reaction solution B;
[0067] Step 3: Add 10 mL of 40% calcium nitrate aqueous solution and 22 mL of 15% sodium silicate solution to the reaction solution B in an ice water bath at 0-10°C, stir the reaction at a stirring rate of 160 rpm for 40 min to obtain the finished product.
[0068] The prepared nano-composite ultra-early strength polycarboxylate water-reducing agent was added to the concrete gel material at 0.2% by weight of the concrete gel material, and the adding method, dosage and product performance of the finished product prepared according to the preparation method of this embodiment were verified:
[0069] The product was tested for net slurry fluidity in accordance with the Test Method for Homogeneity of Concrete Admixtures GB / T8077-2012. The results are shown in Table 2.
[0070] According to the relevant provisions of GB8076-2008 "Concrete Admixtures", the product is tested for strength at various ages. The concrete mix is shown in Table 1:
[0071] Table 1 Concrete mix ratio
[0072] <![CDATA[Cement (kg / m 3 ).]]> <![CDATA[Sand (kg / m 3 )]]> <![CDATA[Stone (kg / m 3 )]]> <![CDATA[Water (kg / m 3 ).]]> 340 800 980 175
[0073] Example 2
[0074] The difference between Example 2 and Example 1 is that the molar ratio of alkylene polyoxyethylene ether and acrylic acid is different, that is, the molar ratio of alkylene polyoxyethylene ether and acrylic acid is 1:4.0, and the other processes are exactly the same.
[0075] Example 3
[0076] The difference between Example 3 and Example 1 is that the molar ratio of alkylene polyoxyethylene ether and acrylic acid is different, that is, the molar ratio of alkylene polyoxyethylene ether and acrylic acid is 1:5.0, and the other processes are exactly the same.
[0077] Example 4
[0078] The difference between Example 4 and Example 1 is that the molar ratio of the functional monomer to the alkylene polyoxyethylene ether is different. In this example, the mass ratio of the functional monomer to the alkylene polyoxyethylene ether is 0.2:10, and the rest of the processes are exactly the same.
[0079] Example 5
[0080] The difference between Example 5 and Example 1 is that the molar ratio of the functional monomer to the alkylene polyoxyethylene ether is different. In this example, the mass ratio of the functional monomer to the alkylene polyoxyethylene ether is 0.4:10, and the rest of the processes are exactly the same.
[0081] Example 6
[0082] The difference between Example 6 and Example 1 is that the type of functional monomer is different, the functional monomer is N,N-dimethylacrylamide, and the rest of the processes are exactly the same.
[0083] Example 7
[0084] The difference between Example 7 and Example 1 is that the type of functional monomer is different, the functional monomer is 2-acrylamide-2-methylpropanesulfonic acid, and the rest of the processes are exactly the same.
[0085] Example 8
[0086] The difference between Example 8 and Example 1 is that the type of functional monomer is different, the functional monomer is N-hydroxymethyl acrylamide, and the rest of the processes are exactly the same.
[0087] Example 9
[0088] The difference between Example 9 and Example 1 is that the ratios of the functional monomer components are different, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid and N-hydroxymethyl acrylamide is 1:2, and the rest of the processes are exactly the same.
[0089] Example 10
[0090] The difference between Example 10 and Example 1 is that the ratio of the components in the functional monomer is different, the mass ratio of 2-acrylamide-2-methylpropanesulfonic acid and N-hydroxymethyl acrylamide is 1:4, and the rest of the processes are exactly the same.
[0091] Embodiment 11
[0092] The difference between Example 11 and Example 1 is that in step 3, the mass ratio of alkylene polyoxyethylene ether, calcium nitrate and sodium silicate is different, that is, the mass ratio of alkylene polyoxyethylene ether, calcium nitrate and sodium silicate is 10:0.08:0.07, and the rest of the processes are exactly the same.
[0093] Example 12
[0094] The difference between Example 12 and Example 1 is that in step 3, the mass ratio of alkylene polyoxyethylene ether, calcium nitrate and sodium silicate is different, that is, the mass ratio of alkylene polyoxyethylene ether, calcium nitrate and sodium silicate is 10:0.12:0.09, and the rest of the processes are exactly the same.
[0095] Embodiment 13
[0096] The difference between Example 13 and Example 1 is that the mud content is different, and the rest of the processes are exactly the same.
[0097] The polycarboxylate water reducer of the present invention is measured according to the "Concrete Admixture Homogeneity Test Method" GB / T8077-2012 for the fluidity of the net slurry, and different masses of montmorillonite are used to replace the corresponding mass of cement by the internal mixing method. The montmorillonite is a 1250 mesh powder sample of Zhejiang Fenghong New Materials Co., Ltd., the water-cement ratio is fixed at 0.29, and the water reducer dosage is 1.0%. The results are shown in Table 2.
[0098] Comparative Example 1
[0099] The difference between Comparative Example 1 and Example 1 is that the polyether macromonomer is different, and the comparative example uses allyl polyoxyethylene polyoxypropylene ether instead of alkylene polyoxyethylene ether. The rest of the processes are exactly the same.
[0100] Comparative Example 2
[0101] The difference between Comparative Example 2 and Example 1 is that the preparation method is different, step 3 is not performed in this comparative example, and the other processes are exactly the same.
[0102] Comparative Example 3
[0103] The difference between Comparative Example 3 and Example 1 is that the functional monomer is different, and sodium methyl methacrylate sulfonate is used as the functional monomer. The rest of the processes are exactly the same.
[0104] Comparative Example 4
[0105] The difference between Comparative Example 4 and Example 1 is that a commercially available polycarboxylic acid high-performance water-reducing agent is directly added to the concrete. The rest of the processes are exactly the same.
[0106] Comparative Example 5
[0107] The difference between Comparative Example 5 and Example 13 is that a commercially available polycarboxylic acid high-performance water-reducing agent is used to replace the polycarboxylic acid water-reducing agent of the present invention. The rest of the processes are exactly the same.
[0108] The demonstration methods and results of the nano-composite ultra-early strength polycarboxylate water reducers prepared in Examples 2 to 13 and the water reducers prepared in Comparative Examples 1 to 5 are equivalent to those in Example 1, and are not described in detail here.
[0109] Implementation effect:
[0110] The product was tested for cement paste fluidity according to the "Concrete Admixture Homogeneity Test Method" GB / T8077-2012, and the cement paste fluidity test results are shown in Table 2. The results show that the addition of the nano-composite ultra-early strength polycarboxylate water-reducing agent has a significant impact on the cement paste fluidity performance index.
[0111] Table 2 Cement paste fluidity test results
[0112]
[0113] As can be seen from Table 2, the net paste fluidity of concrete of Examples 1 to 13 is better than that of concrete of Comparative Examples 1 to 5, indicating that the nano-composite ultra-early strength polycarboxylate water-reducing agent prepared by this method can significantly improve the net paste fluidity of concrete, improve the gradation continuity of mortar, improve the wrapping degree of mortar, improve the strength of concrete, improve the compactness of concrete, and improve the workability of concrete. At the same time, it can reduce the amount of water used for mixing, provide dispersion and water reduction effects, and the fluidity loss over time does not change much, and can provide a good water reduction effect within 120 minutes. The fluidity performance test is better than similar products on the market. Compared with other embodiments, the net paste fluidity of Example 1 is the best. In addition, compared with Example 1, Example 13, Comparative Example 4, and Comparative Example 5, in cement with a mud content of 0, the fluidity of the initial and 30 minutes after the net paste of the embodiment is basically the same when the dosage is consistent with the comparative example. As the mud content increases from 0 to 15%, the embodiment does not need to increase the dosage, and the fluidity can still be guaranteed to remain basically unchanged. The above results strongly prove that the nano polycarboxylic acid particle water reducer of the present invention has excellent water reduction and mud resistance performance.
[0114] The product performance test results are shown in Table 3. The results show that the early compressive strength of concrete products can be significantly improved after the addition of the nano-composite ultra-early strength polycarboxylate water-reducing agent.
[0115] Table 3 Product performance test results
[0116]
[0117] As can be seen from Table 3, compared with the concrete mixed with a commercially available polycarboxylic acid high-performance water-reducing agent, the early and late strength of the concrete are significantly enhanced, and the workability is good; and the various components in the water-reducing agent of the present invention play a synergistic role in the preparation of the water-reducing agent, and synergistically improve the early strength performance and workability and mechanical strength of the concrete. In addition, from the changes in various performance indicators in the test results of Table 3, it can be seen that the various performance indicators of the concrete in each embodiment of the present invention are better than the commercially available products. The nano-composite ultra-early strength polycarboxylic acid water-reducing agent prepared in Examples 1 to 13 is inverted T-shaped, with a molecular weight distribution (Mw / Mn) of 2.0~2.2 and a particle size distribution of 10~30nm. The T-shaped morphology of the molecular chain allows the water-reducing agent molecules to have a strong steric hindrance dispersion effect, while the long polyoxyethylene side chain allows water to enter the cement particles, promotes the hydration of cement, and improves the early strength performance of the water-reducing agent.
[0118] From the comparison between Example 1 and the comparative example, it can be seen that the comparative example does not introduce nano-silicon nano-calcium particles, while Example 1 can stably prepare nano-silicon nano-calcium particles by using calcium nitrate and sodium silicate in an alkaline environment through simple steps, and then the early-strength polycarboxylate water-reducing agent prepared in step 2 is further compounded with the nano-silicon nano-calcium particles to prepare an inverted T-shaped nano-composite ultra-early-strength polycarboxylate water-reducing agent. The introduction of nano-silicon nano-calcium particles promotes the formation of CSH phase during cement hydration. The earlier the CSH phase is formed, the higher the early strength of the hydration product. The two synergize to promote the acceleration of cement hydration rate, increase the number of hydration products, make the cement paste structure more compact, and significantly improve the early strength of concrete. After testing, the 1-day compressive strength ratio of the water-reducing agent of the present application is ≥126%, the 3-day compressive strength ratio is ≥118%, and the standard curing 24 The compressive strength of cement mortar at 17MPa and concrete at 15.7MPa is 17MPa, and the compressive strength of concrete at 90℃ is 73.0MPa (C80 prefabricated pipe pile concrete), which has a significant early strength effect. Moreover, the nano-composite ultra-early strength polycarboxylic acid water-reducing agent particles of the present invention have strong stability and are not easy to agglomerate and precipitate. The total alkali content of the product is ≤2.0%, which avoids reaction with alkali aggregates in concrete and ensures the long-term durability and stability of concrete. The chloride ion content is ≤0.01%, which proves that the product prepared by this method is safe and durable. Moreover, the concrete surface with the water-reducing agent of this application is smooth, the gradation of the mortar is continuous, and the overall structure is more compact, which significantly improves the early strength effect of concrete, and can effectively reduce the shrinkage of concrete, greatly reducing the construction cost. In summary, due to the influence of the type and dosage of the reaction raw materials, the water reducer not only changes the structural morphology of the cement stone, the cement hydration product and the pore structure, but also promotes the formation of the CSH phase during cement hydration through the special inverted T-shaped structure, which is introduced by the nano-silicon and nano-calcium particles. The earlier the CSH phase is formed, the higher the early strength of the hydration product. The two synergize to promote the cement hydration rate to increase, increase the hydration product, make the cement paste structure more compact, and significantly improve the early strength of the concrete. Moreover, the formed water reducer is a nano suspension, which has a certain water-reducing effect, can cover the microstructure pores of the concrete, reduce the porosity, and increase the compactness, thereby further improving the impermeability of the concrete and improving the durability of the concrete. Therefore, the nano-composite ultra-early strength polycarboxylate water reducer particles of the present invention can improve the mechanical properties and shrinkage properties of the concrete as a whole.
[0119] The above examples are for the purpose of illustrating the embodiments disclosed by the present invention and are not to be construed as limitations of the present invention. In addition, the various modifications listed herein and the variations of methods and compositions in the invention are obvious to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been specifically described in conjunction with various specific preferred embodiments of the present invention, it should be understood that the present invention should not be limited to these specific embodiments. In fact, various modifications obvious to those skilled in the art as described above to obtain the invention should be included within the scope of the present invention.
Claims
1. A method for preparing a nano-composite ultra-early strength polycarboxylate water reducer, characterized in that: The following steps are involved: Step 1, add alkylene polyoxyethylene ether, sodium hypophosphite, functional monomer, oxidant and deionized water into a reaction container, stir at 25-45° C. until all are dissolved, to obtain reaction solution A; the molar ratio of the alkylene polyoxyethylene ether to acrylic acid is 1:4.0-5.0; the mass ratio of the functional monomer to the alkylene polyoxyethylene ether is 0.2-0.4:10; the functional monomer is 2-acrylamide-2-methylpropane sulfonic acid and N-hydroxymethyl acrylamide, and the mass ratio of 2-acrylamide-2-methylpropane sulfonic acid to N-hydroxymethyl acrylamide is 1:2-4; Step 2, at 25-45° C., simultaneously add an acrylic acid solution and a vitamin C aqueous solution to a stirred reaction solution A, raise the temperature to 45-65° C. after the addition is completed, and carry out a heat preservation reaction for a period of time, and adjust the reaction system to alkalinity with an alkaline compound and / or an aqueous solution of an alkaline compound to obtain a reaction solution B; Step 3: Add calcium nitrate aqueous solution and sodium silicate aqueous solution to reaction solution B at 0-10° C., stir and react for 30-60 minutes to obtain a finished product.
2. The method for preparing the nano-composite ultra-early strength polycarboxylate water reducer according to claim 1, characterized in that: In step 2, the total time of dropwise addition is controlled within 1 to 3 hours; the insulation reaction temperature is 55° C., the insulation reaction time is 20 to 50 minutes, and the alkaline compound and / or the aqueous solution of the alkaline compound is used to adjust the pH of the reaction system to 9 to 12.
3. The method for preparing the nano-composite ultra-early strength polycarboxylate water-reducing agent according to claim 1, characterized in that: The mass ratio of alkylene polyoxyethylene ether, calcium nitrate and sodium silicate is 10:(0.08-0.12):(0.07-0.09).
4. A nano-composite ultra-early strength polycarboxylate water-reducing agent prepared according to the preparation method according to any one of claims 1 to 3.
5. Use of the nano-composite ultra-early strength polycarboxylate water-reducing agent as claimed in claim 4 in concrete.
6. The use according to claim 5, characterized in that: When the nano composite super-early strength polycarboxylate water reducer is applied to concrete, the solid content is 0.1% to 0.5% of the weight of the concrete gel material.
Citation Information
Patent Citations
Damped water reducing agent and preparation method for concrete
CN102775088A
Super-early strength polycarboxylate water reducing agent and preparation method thereof
CN109438629A
Method for preparing novel polycarboxylic acid nanocrystal nucleus type early-strength water-reducing complexing agent
CN114057425A
Cited By
Early-strength quick-setting polycarboxylate superplasticizer as well as preparation method and application thereof
CN121574313A